Harnessing technological innovation and renewable energy and their impact on environmental pollution in G-20 countries - Siwei Han; Dong Peng; Yuanyuan Guo; Muhammad Umar Aslam; Runguo Xu (Scientific Reports)
Abstract Climate change and environmental degradation are critical global challenges, and the G-20 nations play a pivotal role in addressing these issues due to their substantial contributions to global GDP and carbon emissions. Transitioning toward renewable energy sources is imperative for mitigating CO2 emissions and achieving sustainable development. This study investigates the impact of technological innovation, gross domestic product (GDP), renewable energy consumption, economic freedom, and financial advancement on renewable energy use and environmental pollution levels in G-20 countries from 1995 to 2022. Utilizing the PMG-ARDL dynamic panel method, the research analyzes both long-term and short-term relationships among the variables. The findings reveal that technological innovation significantly boosts renewable energy adoption, with a 1% increase in technological innovation leading to a 0.33% rise in renewable energy use in the long run and a 0.17% increase in the short run. Additionally, increased renewable energy consumption is strongly associated with reductions in CO2 emissions, highlighting its critical role in promoting environmental sustainability. The study emphasizes the importance of policies designed to enhance technological innovation to foster renewable energy usage and reduce environmental pollution. It recommends expanding and reforming the technological sector to align international and local resources with renewable energy initiatives, providing a workable framework for supporting the green growth of institutions and achieving a more sustainable future for G-20 nations. This research contributes to understanding the intricate dynamics of renewable energy transitions, offering actionable insights for policymakers and stakeholders in addressing global environmental challenges.